Pre-Service Physics Teachers' Argumentation in a Model Rocketry Physics Experience - SÜZÜK, EROL (EDAM, 2017)
This study investigates the quality of argumentation developed by a group of pre-service physics teachers' (PSPT) as an indicator of subject matter knowledge on model rocketry physics. The structure of arguments and scientific credibility model was used as a design framework in the study. The inquiry of model rocketry physics was employed in accordance with the model by two groups of participants through model rocketry design and development experience, as well argumentation sessions. The participants were 21 PSPTs from a public university in Turkey. Data were collected through video recordings of the argumentation sequences, which were then transcribed and analyzed using the structure of arguments and scientific credibility model. One of the major results was that PSPTs had a low quality of argumentation. Moreover, this study suggests that designing inquiry-oriented laboratory environments enriched with critical discussion would provide discourse opportunities that support argumentation. Also, PSPTs can be encouraged to support and promote argumentation in their future physics classrooms if they engage in argumentation-based inquiry-oriented laboratories.
Keywords: Pre-service physics teacher education; Argumentation; Argument quality; Subject matter knowledge; Model rocketry; PEDAGOGICAL CONTENT KNOWLEDGE; MATHEMATICAL KNOWLEDGE; SCIENCE-EDUCATION; INQUIRY; DISCOURSE; CHILDREN; QUALITY; REFORM; IMPACT; LEARN